2021
DOI: 10.3390/bioengineering8120190
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Efficacy of Pro- and Anti-Angiogenic Peptide Hydrogels to Treat Age-Related Macular Degeneration

Abstract: Pro-angiogenic and anti-angiogenic peptide hydrogels were evaluated against the standard of care wet age-related macular degeneration (AMD) therapy, Aflibercept (Eylea®). AMD was modeled in rats (laser-induced choroidal neovascularization (CNV) model), where the contralateral eye served as the control. After administration of therapeutics, vasculature was monitored for 14 days to evaluate leakiness. Rats were treated with either a low or high concentration of anti-angiogenic peptide hydrogel (0.02 wt% 8 rats, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Prior work from our group and others has shown that these characteristic SAP nanofibers have dimensions similar to those of selfassembled peptides with distinct mimic architectures (angiogenic, neurogenic, etc.). [14][15][16]23,34,38 Rheometric Analysis of Constructs. Oscillatory rheometric analysis was performed on the peptide hydrogels (Figure 3A 3E,F).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior work from our group and others has shown that these characteristic SAP nanofibers have dimensions similar to those of selfassembled peptides with distinct mimic architectures (angiogenic, neurogenic, etc.). [14][15][16]23,34,38 Rheometric Analysis of Constructs. Oscillatory rheometric analysis was performed on the peptide hydrogels (Figure 3A 3E,F).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…18−21 Therefore, we adopted our biodegradable and benchmarked SAP scaffolds for generation of synthetic growth factors. 22,23 We optimized the SAP-IGF-1 mimic sequence and spacer domains and further studied IGFR binding using in silico analyses, upregulation of the IGF-1/IGFR-activated and proangiogenic Akt signaling pathway in vitro, and angiogenesis within cytocompatible, biocompatible, and biodegradable scaffolds in vivo.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of antiangiogenic active molecules to the hydrogel skeleton is also an attractive topic of study. Acevedo-Jake et al grafted antivascular peptides onto self-assembled peptides to form antiangiogenic polypeptide hydrogels 92 (Figure 5A). In a rat choroidal neovascularization model, the antiangiogenic polypeptide hydrogel showed an improvement trend after 14 days of treatment, which was similar to that of Aflibercept.…”
Section: Application Of Hydrogels In Fundusmentioning
confidence: 99%
“…(A) Schematic of the proposed assembly mechanism of the hydrogels. Reproduced with permission from ref . Copyright 2021 MDPI.…”
Section: Application Of Hydrogels In Ophthalmologymentioning
confidence: 99%